Genetic and Biochemical Diversity of Paenibacillus larvae Isolated from Tunisian Infected Honey Bee Broods - Hamdi, Chadlia (Hindawi Publishing Corporation, 2013)
Paenibacillus larvae is the causative agent of American foulbrood (AFB), a virulent disease of honeybee (Apis mellifera) larvae. In Tunisia, AFB has been detected in many beekeeping areas, where it causes important economic losses, but nothing is known about the diversity of the causing agent. Seventy-five isolates of P. larvae, identified by biochemical tests and 16S rRNA gene sequencing, were obtained from fifteen contaminated broods showing typical AFB symptoms, collected in different locations in the northern part of the country. Using BOX-PCR, a distinct profile of P. larvae with respect to related Paenibacillus species was detected which may be useful for its identification. Some P. larvae-specific bands represented novel potential molecular markers for the species. BOX-PCR fingerprints indicated a relatively high intraspecific diversity among the isolates not described previously with several molecular polymorphisms identifying six genotypes on polyacrylamide gel. Polymorphisms were also detected in several biochemical characters (indol production, nitrate reduction, and methyl red and oxidase tests). Contrary to the relatively high intraspecies molecular and phenotypic diversity, the in vivo virulence of three selected P. larvae genotypes did not differ significantly, suggesting that the genotypic/phenotypic differences are neutral or related to ecological aspects other than virulence.